DESIGN AND SIMULATION OF A ROOFTOP PV SOLAR POWER SYSTEM FOR THE TRAINING ROOM AT PT. PUPUK ISKANDAR MUDA – ACEH - Marzuki; Kartika; Misbahul Jannah; Asran; Arnawan Hasibuan; Misriana; Mulyadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study presents the design and simulation of an on-grid photovoltaic (PV) solar power system for the training room at PT. Pupuk Iskandar Muda (PT. PIM), located in North Aceh, Indonesia. As part of Indonesia’s renewable energy goals, this research explores the potential of rooftop solar installations in supporting the country's energy transition. Using the PVSyst simulation software, the study assesses the technical and economic feasibility of deploying a solar power system tailored to the building’s electricity demands and solar radiation characteristics. The design incorporates monocrystalline and polycrystalline solar panels, and system configurations are optimized based on factors such as panel capacity, inverter specifications, and site-specific conditions. The results indicate that a 2 kWp system can generate up to 2.91 MWh annually, with a performance ratio (PR) of 81.15%, demonstrating the system’s feasibility for sustainable energy use. The findings contribute to understanding the practical applications of rooftop solar power in educational and industrial sectors, providing insights into the potential for broader adoption across similar contexts in Indonesia.